A distopia feminina: a (des)construção das mulheres nos romances Nós e O conto da aia - Scotti, Nathani dos Reis (2025)
This work aims to compare and analyze the construction of the female characters O-90 and I330, from Yevgeny Zamyatin’s We (2017), and Offred/June and Serena Joy, from Margaret Atwood’s The Handmaid’s Tale (2021), in order to elucidate the representative differences between male and female distopic writing. To carry out this study, we highlight the works of authors such as Gregory Claeys (2017), Eric Hobsbawn (2016), Hannah Arendt (2023), Silvia Federici (2023), Hélène Cixous (2022), and bell hooks (2023) as fundamental to understanding the historical, social, and feminist aspects that directly influence the dystopias analyzed. Based on the contributions of these thinkers, we outlined the influences involved in the process of creating patriarchal archetypes in women through literature and how this contributed to the domestication of women over the centuries. In this sense, the effects of this movement also extended to the distinct way in which female characters are portrayed through the eyes of women and men, especially in dystopia, a gender in which, as found in this study, they are fundamental to the transmission of critical social thought.